Elements in the Development of a Production Process for Modified Vaccinia Virus Ankara - Volker Sandig (Microorganisms, 2013)
The production of several viral vaccines depends on chicken embryo fibroblasts or embryonated chicken eggs. To replace this logistically demanding substrate, we created continuous anatine suspension cell lines (CR and CR.pIX), developed chemically-defined media, and established production processes for different vaccine viruses. One of the processes investigated in greater detail was developed for modified vaccinia virus Ankara (MVA). MVA is highly attenuated for human recipients and an efficient vector for reactogenic expression of foreign genes. Because direct cell-to-cell spread is one important mechanism for vaccinia virus replication, cultivation of MVA in bioreactors is facilitated if cell aggregates are induced after infection. This dependency may be the mechanism behind our observation that a novel viral genotype (MVA-CR) accumulates with serial passage in suspension cultures. Sequencing of a major part of the genomic DNA of the new strain revealed point mutations in three genes. We hypothesize that these changes confer an advantage because they may allow a greater fraction of MVA-CR viruses to escape the host cells for infection of distant targets. Production and purification of MVA-based vaccines may be simplified by this combination of designed avian cell line, chemically defined media and the novel virus strain.